Rectoperineal Fistula Presented 5 Months After Repair of Severe Obstetric Perineal Laceration: A Case Report - Ohara, Yusuke; Enomoto, Tsuyoshi; Owada, Yohei; Hisakura, Katsuji; Akashi, Yoshimasa; Ogawa, Koichi; Doi, Manami; Takahashi, Kazuhiro; Shimomura, Osamu; Furuya, Kinji; Kim, Jaejeong; Hashimoto, Shinji; et al. (Frontiers in Surgery, 2021)
Introduction Obstetric severe perineal laceration can frequently occur as a surgical site infection (SSI), which sometimes leads to rectovaginal fistula after repair. We encountered a rare case of a rectoperineal fistula five months after repair of a severe perineal laceration. Case presentation The patient was a 39-year-old woman who underwent repair of a fourth-degree perineal laceration after vaginal delivery. Five months after primary repair, she presented with perineal swelling and pain followed by uncontrollable flatulence or passage of feces at the perineum, which was finally diagnosed as a rectoperineal fistula. Transperineal repair with fistulous tract excision was performed for the rectoperineal fistula. Closure of the rectum, perineal body, and vagina was performed layer-by-layer constructing a thick perineum to prevent anal dysfunction. The fistula was successfully closed, and the patient did not show any symptoms of fecal incontinence six months after surgery. Discussion As the rectoperineal fistula might have resulted in SSI at the primary repair of the obstetric injury, the delayed occurrence of the rectoperineal fistula was unusual. A perineal approach should be performed for complete fistulous tract excision, reconstruction of a robust perineal structure, and preservation of anal sphincter function.